2002
DOI: 10.1021/ja017482e
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Ruthenium(II) Diamine Anticancer Complexes:  Arene-Nucleobase Stacking and Stereospecific Hydrogen-Bonding in Guanine Adducts

Abstract: Organometallic ruthenium(II) arene anticancer complexes of the type [(eta(6)-arene)Ru(II)(en)Cl][PF(6)] (en = ethylenediamine) specifically target guanine bases of DNA oligomers and form monofunctional adducts (Morris, R., et al. J. Med. Chem. 2001). We have determined the structures of monofunctional adducts of the "piano-stool" complexes [(eta(6)-Bip)Ru(II)(en)Cl][PF(6)] (1, Bip = biphenyl), [(eta(6)-THA)Ru(II)(en)Cl][PF(6)] (2, THA = 5,8,9,10-tetrahydroanthracene), and [(eta(6)-DHA)Ru(II)(en)Cl][PF(6)] (3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
441
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 445 publications
(466 citation statements)
references
References 87 publications
19
441
1
5
Order By: Relevance
“…The careful evaluation of the TOCSY spectrum together with the COSY spectrum on the sample of pH = 8.52 ( Fig. 7) containing an (N,N) chelator [56] while a slight upfield shift was detected for [Ru( 6 -pcym)(acac)Cl] (acac = acetylacetonate) containing an (O,O) chelating set [57] upon reacting with 9-ethylguanine. Regarding the rate of the interaction the spectra suggest that this is fast (in accordance with earlier findings [56,57] ) as no significant change in the ratio of the major signals in the function of time can be seen, however, two additional minor species also seem to be formed at a much slower rate.…”
Section: Nmr Resultsmentioning
confidence: 99%
“…The careful evaluation of the TOCSY spectrum together with the COSY spectrum on the sample of pH = 8.52 ( Fig. 7) containing an (N,N) chelator [56] while a slight upfield shift was detected for [Ru( 6 -pcym)(acac)Cl] (acac = acetylacetonate) containing an (O,O) chelating set [57] upon reacting with 9-ethylguanine. Regarding the rate of the interaction the spectra suggest that this is fast (in accordance with earlier findings [56,57] ) as no significant change in the ratio of the major signals in the function of time can be seen, however, two additional minor species also seem to be formed at a much slower rate.…”
Section: Nmr Resultsmentioning
confidence: 99%
“…Eight triplet excited states were calculated by TD-DFT using the lowest-lying triplet state geometry. The electronic distribution and the localization of the singlet and triplet excited states were visualized using the electron density difference maps (EDDMs (10) were prepared in three ways:…”
Section: Methodsmentioning
confidence: 99%
“…9,10 A crucial step in one mode of activation of these anticancer agents is generally the initial aquation of the Ru-Z bond to form a more reactive aqua specie, 11 which subsequently can bind to biological targets. It has been shown previously that fast hydrolysis rates can usually lead to non-cytotoxic complexes, whereas very slow hydrolysis rates often lead to low in vitro cytotoxicity, 10,12 for example the complex [(η 6 -hmb)Ru(en)Py] 2+ does not hydrolyze in aqueous solution at 310 K and is not cytotoxic (IC 50 value > 100 µM). 11 We have recently shown that one key strategy to increase the potential of this class of complexes is to activate the release of the monodentate ligand Z by photoirradiation to promote the formation of the aqua adduct, which would otherwise not form in the dark.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations